Mid-infrared vibrational study of deuterium-containing PAH variants - Buragohain, Mridusmita; Pathak, Amit; Sarre, Peter; Onaka, Takashi; Sakon, Itsuki (Elsevier, 2016)
Polycyclic Aromatic Hydrocarbon (PAH) molecules have been long proposed to be a major carrier of ‘Unidentified Infrared’ (UIR) emission bands that have been observed ubiquitously in various astrophysical environments. These molecules can potentially be an efficient reservoir of deuterium. Once the infrared properties of the deuteriumcontaining PAHs are well understood both experimentally and theoretically, the interstellar UIR bands can be used as a valuable tool to infer the cause of the deuterium depletion in the ISM.